PERTUMBUHAN VEGETATIF TANAMAN TOMAT (LYCOPERSICUM ESCULENTUM MILL.) DARI BENIH LAMA YANG DIINDUKSI KUAT MEDAN MAGNET 0,1 MT, 0,2 MT, DAN 0,3 MT - Novitasari, Vina; Agustrina, Rochmah; Irawan, Bambang; Yulianty, Yulianty (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTTomatoes (Lycopersicum esculentum Mill.) horticultural which are very good for consumption as well as industrial materials. However, the cultivation of tomatoes still faces many obstacles, one of them is the seed. The quality of old seeds decreases with age of seeds, so that it will affect a crop production. This study aims to determine whether the magnetic field strength can improve tomato plant vigor. The study was conducted using a completely randomized design (CRD) of one factor, the induction of a magnetic field consisting of 3 levels, namely 0.1 mT (M0.1), 0.2 mT (M0.2), 0.3 mT (M0,3) for 7 minutes 48 seconds. This study uses two controls; positive control the new seed (Sn) and negative control was the old seed (So) from not being given a magnetic field treatment each experiment unit is repeated 5 times. The parameters measured were plant height, chlorophyll content, and carbohydrate content. The data obtained were analyzed. If there was a difference between treatments, it was continued with the smallest difference between treatments using the Tukey's test at the 5% level. The results of the analysis prove that the magnetic field induction of the old seed can increase seed vigor, causing plant height, chlorophyll and carbohydrate content to be the same as plants from new seeds. Keywords: tomatoes, old seeds, strong magnetic field